Cross-Shear Test for geosynthetic-reinforced asphalt. (January 2023) - Roodi, G.H.; Zornberg, J.G.; Yang, L.; Kumar, V.V.
Abstract: Geosynthetics have been used within hot mix asphalt to provide a broad range of benefits, including those of controlling the development of reflective cracks into structural overlays, minimizing moisture infiltration, and increasing structural capacity. The performance of geosynthetic-reinforced asphalt has been evaluated under several loading modes through a variety of experimental procedures (e.g., three- and four-point bending, interface shear, wheel tracking test). However, limited research has been conducted to evaluate the performance of geosynthetic-reinforced asphalt under the shear loading mode that governs the reflection of cracks into structural overlays, which is shearing across the geosynthetic plane (cross-shear loading). In this study, an experimental procedure was developed to test the unreinforced and geosynthetic-reinforced asphalt subjected to cross-shear loading. Specifically, monotonic and cyclic cross-shear tests were conducted on control (unreinforced) asphalt specimens as well as asphalt specimens that were reinforced with four different geosynthetic reinforcements, including two polymeric and two glass products. The results show that all the geosynthetic reinforcements adopted in this study led to a significant improvement in the performance of asphalt specimens, though differences could be identified on the type of benefits provided by different geosynthetic products. Specifically, the geosynthetic with the highest tensile stiffness was found to provide the most significant benefits before crack development, but negligible post-cracking benefit due to its low elongation at break. On the other hand, comparatively less stiff geosynthetics showed significantly high post-cracking benefits. Under cyclic loading, while all reinforced asphalt specimens exhibited superior performance against the control specimens, the polymer-reinforced specimens showed comparatively better performance than the glass-reinforced specimens due to the better fatigue resistance of polymers as compared to glass.